Primary percutaneous coronary intervention in a patient with anomalous origin of the left coronary artery from the opposite sinus of Valsalva and left main coronary artery occlusion - Čanković Milenko; Čanji Tibor; Debeljački Dragan; Komazec Nikola; Petrović Milovan; Velicki Lazar (Vojnosanitetski Pregled)
Introduction. Congenital coronary anomalies are detected in about 5% of all performed coronarographies. Coronary artery (CA) anomalies (CAA), considered to be of great risk, are the ones where the CA arises from the opposite sinus (anomalous origination of CA from opposite sinus, ACA-OS) of Valsalva. These anomalies are detected in about 1% of cases. This report shows a unique case of a patient with anterior wall ST-elevation myocardial infarction (STEMI) caused by left main CA (LMCA) occlusion, which arose from the right coronary cusp and had an interarterial course, successfully treated with primary percutaneous coronary intervention (PCI). Case report. A 46-year-old male patient was admitted to the hospital due to STEMI of the anterior region. On admission, the patient was hypertensive (150/100 mmHg) in sinus rhythm (heart rate 70/min), Killip I. After the initial examination and admitting dual antiplatelet therapy, the patient underwent urgent coronarography. Coronarography was performed using the transradial approach. The right CA had no significant stenosis and was easily cannulated, whereas the left CA could not be cannulated at the usual position. Attempts to cannulate the left CA with multiple catheters of various curves were unsuccessful. The conclusion was that there was a CA anomaly, and the cannulation of the anomalous left CA, which arose from the opposite (right) coronary cusp (anomalous aortic origin of the left CA, AAOLCA), was successfully performed with a Multipurpose catheter. Moreover, the LMCA was occluded in the distal segment. Two drug-eluting stents (DES) were implanted, but the patient developed the no-reflow phenomenon and cardiogenic shock. After the patient was stabilized, computed tomography (CT) coronarography was performed, and AAOLCA with an interarterial course was registered. During the follow-up period, single photon emission computed tomography (SPECT) was per-formed, and in the staged procedure, a stent was implanted into the proximal circumflex artery using the T and protrusion (TAP) technique. Conclusion. Patients with STEMI and the anomalies of CAs are very rare. As such, these patients represent a great challenge for revascularization. Possessing the knowledge of anatomic varieties is paramount when it comes to these patients to treat them adequately with primary PCI.